Hymen protection and the sexual practices, perceptions, and attitudes of female university students from Lebanon. Issue 2 (18th August 2017) - El Kak, Faysal; El Salibi, Noura; Yasmine, Rola; Ghandour, Lilian
Abstract: Objective: To investigate associations between hymen protection and women's alternative sexual practices, perceptions, and attitudes. Methods: A cross‐sectional online survey was administered among university students (aged 18–30 years) in Lebanon between April 30 and August 31, 2012. The present analysis focused on female students who had engaged in oral/anal sex. Results: Among 416 included women, 163 (39.3%) reported anal/oral sex to protect their hymen. Women ever concerned with hymen protection were less likely to be non‐Lebanese and not religious/spiritual, but more likely to report unwanted sexual activities, a relationship in which they felt things were moving too fast physically, and to feel guilty about sexual feelings (all P< 0.01). They were two‐to‐three times more likely to agree that it is harder to refuse sex after the first time and that oral sex is not as big of a deal as sexual intercourse (both P< 0.001). Concerned women who later engaged in vaginal sex (n=75) were less religious and more accepting of premarital sex than were those who continued to protect their hymen (n=88; all P< 0.005). Conclusion: Women concerned about hymen‐breaking engage in alternative sexual practices, yet experience pressure, guilt, worry, and indecisiveness regarding their sex‐related decisions. The navigation of sexual decisions is a more vulnerable process for these women because of prevailing patriarchal values and discriminating gender norms in Lebanon. Abstract : Patriarchal values and cultural norms in Lebanon make the navigation of sexual decisions a more vulnerable process for women concerned about hymen‐breaking.